Croissance économique des pays émergents et géographie mondiale des pierres précieuses - Remy Canavesio (EchoGéo)
Extraction activities evolution is more and more dependent on the increase of demand in the emerging countries. The consequences of this growth on the gemstone mining activities are complex. The gemstone market is very special and the demand depends on the historic and cultural situation of every country. Moreover, for precious stones like rubby and sapphire, the supply coming from this emerging country is also affected by the social and economic changes. As the small scale mining is widely held in this activity, people that are becoming richer are less interested in that kind of job. In Sri Lanka and Burma, the depletion of many deposits is an other challenge. Finally, if new diamonds deposits of Canada, Russia and Australia are supplying the growth of the diamond market, Est Africa looks like the new « Eldorado » for the other gemstones. Geologic, economic, social and political context of these countries are perfectly adapted for the development of new gemstone small scall mining areas.